Early Identification and Intervention of Underachievement among Gifted Students - Sovy, Rosiyatus; Ramanda, Peni; Ramdhan, Septi Nuririanti; Sarah , Siti; Amanina, Farah Ayu (Quanta : Jurnal Kajian Bimbingan dan Konseling dalam Pendidikan, 2025)
This study aims to identify the underlying factors contributing to underachievement in gifted students and to formulate early intervention strategies that schools can implement. A qualitative case study approach focused on a high school student with strong academic potential who experienced a significant decline in academic performance, placing them at risk of not being promoted to the next grade. Data were collected through in-depth interviews, observations, and document analysis. The findings reveal that the main factors contributing to underachievement include a lack of interest in certain subjects, an unsupportive social environment, and unstable family dynamics caused by the absence of a father figure. The study concludes that early identification and collaborative interventions involving subject teachers, school counselors, and parents play a crucial role in helping gifted students regain their academic performance in line with their potential. The implications of this study serve as a reference for teachers in implementing early screening and targeted intervention programs for gifted students experiencing underachievement.